Effects of 440-Hz vs. 432-Hz preferred music frequencies, during warm-up, on intermittent anaerobic speed test performance in men and women kickboxers: a double-blind crossover study - Jebabli, Nidhal; Boujabli, Manar; Khlifi, Mariem; Ouerghi, Nejmeddine; Bouassida, Anissa; Ben Abderrahman, Abderraouf; van den Tillaar, Roland (PeerJ, 2025)
Background Preferred music has been shown to enhance psychological and physiological parameters in order to increase physical performance in high intensity exercises. However, the effects of preferred music are less conclusive with different frequencies. The present study assessed the effects of listening to preferred music during warm-up at different frequencies on physical performance and psychophysiological responses specific in male and female kickboxers. Methods In a double-blind crossover study design, fifteen men and thirteen women kickboxers randomly performed the intermittent kickboxing anaerobic speed test (IKAST) after listening to preferred music around 440 Hz (PM44Hz), or 432 Hz (PM432Hz) frequencies or no music during warm-up. Physical performance indices, heart rate, blood lactate, rating of perceived exertion (RPE) and feeling scale (FS) were measured. Results Warm-up with PM440 Hz significantly improved IKAST performance indices with the highest impact velocity and FS, lowest mean heart rate and RPE, followed by PM432 Hz for both sexes compared to the control condition. For sex interaction, men had lower heart rate with PM440Hz, women the lowest with PM432Hz. In addition, women had higher positive feeling scale with PM440Hz, while men did not experience any significant change between the two musical conditions. Conclusion PM440Hz during warm-up was found to be more effective in improving specific performance, positive mood with a potential dissociation from discomfort during the test. Also, women were more affected by the music frequency difference compared to men.
Keywords: Fast tempo music; Tone frequencies; Specific exercise; Psychophysiological responses; Physical performance